Protocol on utilizing murine gastric cancer organoids for modeling subcutaneous, orthotopic primary, and liver metastatic disease in mice - Joshua Konecnik; Ryan N. O’Keefe; Kiruthiga Raghunathan; Saumya P. Jacob; Megan O’Brien; Anne Huber; Purva Trivedi; Christine Dijkstra; Amr H. Allam; Michael Buchert; Matthias Ernst; Moritz F. Eissmann (STAR Protocols)
Summary: Tumor initiation, growth, and spread are influenced by cancer cell intrinsic and tissue microenvironment factors of the organ the tumor resides in. Here, we provide a protocol on utilizing murine gastric cancer (GC) organoids as transplantable mouse models for subcutaneous, orthotopic primary, and liver metastatic disease. We provide detailed instructions for organoid expansion; processing of GC organoids; and their subsequent subcutaneous, intra-stomach wall, and intra-splenic transplantation. We then detail steps for post-procedure tumor and metastasis monitoring and outcomes.For complete details on the use and execution of this protocol, please refer to Huber et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.